Geographically Distributed Real-Time Simulation of a Hierarchical Control Architecture for Isolated Microgrids - Marco Menga; Lucio Barbato; Gianpatrizio Bianco; Luigi Mascolo; Gabriele Nardelli; Francesco Renna; Gianluca Sapienza; Chiara Micillo; Sergio Bruno; Cosimo Iurlaro; Massimo La Scala (IEEE Open Journal of Power Electronics)
In the energy transition scenario, the security of small isolated electrical networks is challenged by the pervasive Renewable Energy Sources (RES) penetration. This paper presents a hierarchical control architecture designed within the framework of an Italian industrial research project. The proposed control architecture aims to allocate adequate operating reserve during the operation of isolated microgrids in the presence of high RES penetration. To validate its performances under realistic conditions, the architecture was implemented and tested in a Hardware-in-the-Loop simulation environment, which employed Geographically Distributed Real-Time Simulation to exploit the software and hardware facilities of two separate laboratories. The set-up serves as a cyber-physical demonstrator, enabling the assessment of the readiness level and effectiveness of the proposed control architecture in ensuring the secure operation of the isolated electrical network of a real Italian small island under vulnerable operating conditions.